2018
DOI: 10.1097/sla.0000000000002095
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hospital Volume on Breast Cancer Mortality

Abstract: Objective The aim of this study was to determine whether hospital volume was associated with mortality in breast cancer, and what thresholds of case volume impacted survival. Background Prior literature has demonstrated improved survival with treatment at high volume centers among less common cancers requiring technically complex surgery. Methods All adults (18 to 90 years) with stages 0–III unilateral breast cancer diagnosed from 2004 to 2012 were identified from the American College of Surgeons National … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 28 publications
3
32
0
1
Order By: Relevance
“…Another study found that higher surgeon and hospital volume significantly predicted lower subsequent re-operation after breast conserving surgery and after adjustment for socio-demographic and clinical variables [ 97 ]. A recent study from the United States reported that treatment at high volume centres is associated with improved survival for breast cancer patients regardless of stage, and that high case volume could serve as a proxy for the institutional infrastructure required to deliver complex multidisciplinary breast cancer treatment [ 98 ]. Looking at multidisciplinary aspects, an observational cohort study evaluated the effects on breast cancer survival on nearly 14,000 women in Scotland, and found MDT working was associated with a 18% lower breast cancer mortality at 5 years [ 99 ].…”
Section: Supporting Evidence and Informationmentioning
confidence: 99%
“…Another study found that higher surgeon and hospital volume significantly predicted lower subsequent re-operation after breast conserving surgery and after adjustment for socio-demographic and clinical variables [ 97 ]. A recent study from the United States reported that treatment at high volume centres is associated with improved survival for breast cancer patients regardless of stage, and that high case volume could serve as a proxy for the institutional infrastructure required to deliver complex multidisciplinary breast cancer treatment [ 98 ]. Looking at multidisciplinary aspects, an observational cohort study evaluated the effects on breast cancer survival on nearly 14,000 women in Scotland, and found MDT working was associated with a 18% lower breast cancer mortality at 5 years [ 99 ].…”
Section: Supporting Evidence and Informationmentioning
confidence: 99%
“…Studies suggest breast cancer patients treated by oncology specialists or by high‐volume providers or centers are more likely to receive guideline‐concordant care and have higher survival rates than patients treated by non‐specialists or at low‐volume centers 9–11 . A review of the National Cancer Database (NCDB) suggests that treatment at a high‐volume center (defined as annual cases ≥298) resulted in an 11% reduction in mortality compared to treatment at low‐volume centers 12 . Notably, NHB women in the study did not appear to have any improvement in survival when treated at high‐volume centers compared with low‐volume centers 12 .…”
Section: Introductionmentioning
confidence: 99%
“…A review of the National Cancer Database (NCDB) suggests that treatment at a high‐volume center (defined as annual cases ≥298) resulted in an 11% reduction in mortality compared to treatment at low‐volume centers 12 . Notably, NHB women in the study did not appear to have any improvement in survival when treated at high‐volume centers compared with low‐volume centers 12 . In the aforementioned study, hospital volume categories were based on the relationship between annual hospital volume and survival after controlling for potential confounding variables.…”
Section: Introductionmentioning
confidence: 99%
“…Higher volume facilities may have longer wait times for consultations, resulting in delays to surgery or starting NAC. However, treatment at high volume centers has been shown to be associated with improved OS . It is unclear why higher income was associated with longer treatment times, but the most likely reason is that these patients have the financial means to obtain multiple opinions at different facilities, which lengthens the time from diagnosis to treatment initiation .…”
Section: Discussionmentioning
confidence: 99%